Exploring the Impact of Digital Transformation on Brand Loyalty in Emerging Markets - Rahmayeni, Zulwida; Khairi, Awalul; Susanti, Erna (Jurnal Informatika Ekonomi Bisnis, 2025)
This study examines the impact of digital transformation on brand loyalty in emerging markets, where digital adoption is expanding but remains uneven across consumer segments. The research aims to analyze whether digital transformation initiatives contribute to stronger brand loyalty by enhancing consumer experiences and long-term engagement. A quantitative research design is employed using a cross-sectional survey of consumers who interact with brands implementing digital platforms, mobile applications, and online engagement tools. Data are collected through a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the proposed relationship. The results indicate that digital transformation has a positive and statistically significant effect on brand loyalty, demonstrating that higher levels of perceived digital integration and responsiveness are associated with stronger consumer commitment and repeat purchase intentions. The findings highlight that digital transformation functions not only as an operational improvement but also as a strategic instrument for strengthening brand–consumer relationships. This study provides practical insights for firms in emerging markets to position digital transformation as a core branding strategy and contributes empirically to the limited literature on digital transformation and brand loyalty within emerging market contexts.